2020
DOI: 10.1017/s0007114520002731
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of the Mediterranean diet among adolescents: evidence from an Eastern Mediterranean Country

Abstract: At the time when the health benefits of the Mediterranean diet (MD) are pervasively recognized, a paradoxical observation is the decreasing adherence to this dietary pattern in its native countries. This study aims to investigate temporal trends in adherence to the MD among adolescents (10-19 years old) in Lebanon. Data were drawn from three national cross-sectional surveys conducted at three points in time: 1997 (n = 2004), 2009 (n = 3656), and 2015 (n = 1204). Dietary intake was assessed using 24-hr dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…More alarming is the observed trend in SSB consumption in Lebanon. A recent national study documented an increase in SSB among Lebanese adolescents, from 241.4 g/day in 1997 to 321.7 g/day in 2009 and 301.6 g/day in 2015 (Naja et al, 2021).…”
Section: Sodium and Fructose Intake Levels In Lebanonmentioning
confidence: 99%
“…More alarming is the observed trend in SSB consumption in Lebanon. A recent national study documented an increase in SSB among Lebanese adolescents, from 241.4 g/day in 1997 to 321.7 g/day in 2009 and 301.6 g/day in 2015 (Naja et al, 2021).…”
Section: Sodium and Fructose Intake Levels In Lebanonmentioning
confidence: 99%
“…This interesting finding may be due to the fact that our sample showed low MD adherence according to the MDSS, even in those countries known for their traditional MD patterns, such as Spain and Italy, in agreement with previous findings of low MD adherence and food knowledge among healthcare students from Italy [ 41 ], Spain [ 42 ], and Turkey [ 43 ]. A decline in MD adherence of the general population in the Mediterranean area, and especially of younger generations, is widely recognized [ 44 , 45 , 46 ]. It has been reported that potential factors resulting in moving away from the MD model include globalization, a transition to Western habits, modernization and changes in lifestyle and environment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Naja et al (2020) noted a significant decline in adherence to the Mediterranean diet among Lebanese adolescents between 1997 and 2015, from 35.03% to 27.63% respectively, using country-specific indices. This decline in adherence to the Mediterranean diet was shown to be largely driven by the decreasing consumption of whole fruits and vegetables from around 6% and 6.5% of total energy intake respectively in 1997 to around 3.4% and 3.8% respectively in 2015, and the increasing intake in parallel of "unhealthy" foods such as salty snacks and sugar sweetened beverages contributing respectively to 7.6% and 7% of adolescents' total energy intake [22]. Gulf countries have also reported a rapid change in dietary habits and lifestyle over the past 3 decades whereby the traditional diet consisting of dates, milk, rice, brown bread, fish, and vegetables shifted to a more westernized type of diet [20].…”
Section: Nutrition Transition and Diabetes In The Middle Eastern And North African (Mena) Regionmentioning
confidence: 99%